A regional assessment of the intra-Carboniferous play of Northern England - Fraser,AJ; Nash,DF; Steele,RP; Ebdon,CC (Geological Society Special Publication, 1990)
Hydrocarbons have been produced from the Carboniferous of the East Midlands since the 1920s. Some 30 discoveries have been made to date and although field sizes are generally small, the relatively low costs have made exploration and development an attractive commercial proposition. Many of the factors which contribute to success in the East Midlands occur in other basins in Northern England but have not produced significant hydrocarbon accumulations. This paper examines the key attributes of the intra-Carboniferous play and through an integrated regional geological framework contrasts the successful East Midlands oil province with the other Carboniferous basins of Northern England. © 1990 The Geological Society.